Innovation Performance of Organization - Branislav Micieta; Martin Gaso; Martin Krajcovic (Communications - Scientific letters of the University of Zilina, 2014)
Globalization has confirmed that the competitive ability of organizations is conditioned by the successful development of innovations. Innovation management and development of innovative potential of organizations are becoming a scientific problem, since the existing approaches in this area do not have satisfactory results. The paper presents a new approach to enhancing innovation performance of the organization that is built on a systematic examination of possible innovation potential of the organization and purposeful creation of a suitable innovative environment in the organization.